MULHERES DE CARREIRA E FAMÍLIA - Lievore, Maria Eduarda; de Resende Miranda, João Irineu (Revista Feminismos, 2022)
RESENHA DO LIVRO: GOLDIN, Claudia. Career and Family: Women’s Century-Long Journey toward Equity. Princeton University Press, 2021. V1 p. 342.